Phone Banking for Dukakis Campaign - Watkins, Howard::::::::: (1988)
Two Neighborhood brothers with Princess Robin Watkins and LA Dodger Adam Watkins ready for Halloween; Howard Watkins wearing No Reagan mask and tee shirt